2005
DOI: 10.1111/j.0737-1209.2005.220405.x
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Transtheoretical Model to Physical Activity in Family Caregivers in Taiwan

Abstract: Since this is the first TTM study in Taiwan, continued TTM testing is needed to adequately determine the applicability of the TTM and to identify the most effective theory-based physical activity interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 48 publications
2
20
1
Order By: Relevance
“…These results are also supported by Tung, Gillett, and Pattillo (2005), who found that among Taiwanese caregivers of patients with mental illness, the perceived cons measure was unable to differentiate stages. In two other transtheoretical model studies conducted in Asian countries, the researchers also indicated no significant stage differences in perceived cons in young Chinese (Callaghan, Eves, Norman, Chang, & Lung, 2002) and Japanese women (Wakui et al, 2002).…”
Section: Relationships Among Stages Of Change and Transtheoretical Mosupporting
confidence: 68%
“…These results are also supported by Tung, Gillett, and Pattillo (2005), who found that among Taiwanese caregivers of patients with mental illness, the perceived cons measure was unable to differentiate stages. In two other transtheoretical model studies conducted in Asian countries, the researchers also indicated no significant stage differences in perceived cons in young Chinese (Callaghan, Eves, Norman, Chang, & Lung, 2002) and Japanese women (Wakui et al, 2002).…”
Section: Relationships Among Stages Of Change and Transtheoretical Mosupporting
confidence: 68%
“…A higher score on the exercise benefits scale indicates perception of greater benefits from engaging in exercise, while a lower score on the exercise barrier scale indicates perception of fewer barriers to engaging in exercise. The Chinese version of these two scales showed a high degree of internal consistency, with Cronbach's alphas of 0.97 and 0.93, respectively (Tung et al, 2005).…”
Section: Outcome Measuresmentioning
confidence: 97%
“…The two week testretest reliability of the scale was 0.79 (Courneya, 1995). This scale was translated into Chinese by Tung using forwardtranslation, back-translation, and panel review, and showed good acceptance (Tung et al, 2005).…”
Section: Outcome Measuresmentioning
confidence: 98%
See 1 more Smart Citation
“…The 2-week test-retest reliability was 0Á79 (Courneya 1995). This scale was translated into Chinese by Tung (2003) using forward-translation, back-translation and panel review and showed good acceptance (Tung 2003).…”
Section: Instrumentsmentioning
confidence: 96%